Added Value and Sustainability of Coffee Skin Waste Processing Business in Ngarip Village, Ulubelu District, Tanggamus Regency - Fahrul Rozi Maulana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Coffee husks, whether wet or dry processed, contain nutrients that are beneficial for plant growth. Coffee husk waste is known to contain 1.27% nitrogen, 0.06% phosphorus, and 2.46% potassium. Based on this potential, various previous studies have examined the use of coffee husk waste as a raw material for composting. This study aims to calculate and analyze the resulting added value and evaluate the sustainability of the coffee husk waste processing business at Pertaganik Bestari, Ngarip Village, Ulubelu District. The value-added calculation was conducted using the Hayami method, referring to prices prevailing in the analysis year. The results showed a value-added ratio of 75.46%, labor contribution of 8.48%, and a profit margin of 91.51%. The sustainability assessment, based on three criteria: value-added ratio, labor contribution, and profit margin, indicates that this business has a high level of sustainability and is prospective for future development.